Pengaruh Latihan Endurance Terhadap Vo2 Max Di Sekolah Sepak Bola Desa Haurkolot - Tikfi Diani Kartika; Yohanes Deo Fau; Amin Zakari; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Football is a branch of big ball games with the predominance of endurance, strength and speed. Soccer players must have good endurance so they don't get tired easily, in this case it requires a lot of VO2 Max. 12 minutes of running practice can increase the endurance of soccer players which has an impact on increasing VO2 Max. The purpose of this study was to determine the effect of endurance training on VO2 max at the Haurkolot Village Football School.Methods: This research method uses a pre-experimental with one group pretest posttest design with a sample of 30 people with a purposive sampling technique. The data collected is VO2 Max which is measured using a bleep test. Measurements were made twice, before and after treatment. The intervention carried out was running endurance exercise for 12 minutes. The data analysis technique uses the Paired Sample Test.Results: The results of the study obtained an average VO2 Max value before endurance exercise obtained an average value = 41.073, after endurance exercise obtained an average value = 50.237 with a significance value of 0.000.Conclusion: Based on the results of this study it can be concluded that there is a significant effect of endurance training on VO2 Max at the Haurkolot Village Football School. Soccer players are expected to be able to maintain a training routine by having high motivation during training so that they have high integrity to do a 12-minute running exercise (cooper test) in order to increase endurance so as to increase VO2Max.